Potensi Ekstrak Etanol (96%) Jahe Merah (Zingiber Officinale Var. Rubrum) dalam Memperbaiki Fungsi Hormon, Ovarium dan Resistensi Insulin pada Tikus Wistar Model Polycystic Ovarian Syndrome - Siti Mudrikatin; Edy Anas Ahmadi (Lembaga Pengembangan Kinerja Dosen, 2024)
Previous studies have shown that red ginger has the potential to treat PCOS because it has been proven to be able to reduce serum FSH, LH and estradiol and testosterone, inhibit the cyclooxygenase pathway, change the pituitary axis, inhibit lipoxygenase expression in various animal studies. The purpose of this study is to prove the potential of red ginger extract as a regulator of anti-androgenic, ovulation, estrogenic activity and reduce insulin resistance. The research design used was for experimental research using a post-test-only control group design. And for the analysis of the potential bioactivity of red ginger extract as an immunomodulatory agent computationally (Insilico). Animal care was carried out in the Pharmacology and Biomedicine Laboratory and has received approval from the Ethics Committee. The sample used was a female Wistar rat on the 56th day of the experiment (after modeling). All treatments were given orally for 28 times. Independent variable = Red ginger extract. Dependent variable = Dependent variables are 1. Hormones: Testosterone, LH, FSH 2. ovarian inflammation activation (PPARγ activation and anti-inflammatory cytokines IL-4 and ROS, NFKB, TNF a. 3. Insulin resistance (insulin, glucose, HOMA IR) and 4 Lipid profile (TG, HDL, LDL, cholesterol). Control variables are: 1) Gender; 2) Age; 3) Strain; 4) Food and beverage intake; 5) Maintenance and care. Quantitative and qualitative research data. using parametric tests, namely One-Way ANOVA after meeting the requirements for normal data distribution and the same data variance. The One-Way ANOVA statistical test is continued with the Tuckey test to determine the differences in each group.